Integrasi Konsep Perbankan Syariah dengan Pengembangan Badan Usaha Milik Desa (BUMdes) Desa Maredan Siak - Adiyes Putra; Yusri Yusri; Nurhasanah Nurhasanah; Mukhyar Mukhyar; Ali Wardana; Mohammad Fikri Sulthoni; Herlina Herlina (Al-Mutharahah: Jurnal Penelitian dan Kajian Sosial Keagamaan, 2019)
The BUMdes business unit for saving and borrowing from Maredan Siak Village is still a conventional model where the profit is applied according to the practice of interest. Interest according to the fatwa of the Indonesian Ulema Council (MUI) has been declared extinct. Riba is very determined and forbidden by Islam. Therefore, for a person, the theoretical concept of sharia may not be the practice of saving and lending that contain usury. Besides, the unity of Islamic values ​​with Malaysian culture should strengthen BUMdes programs in Siak Regency. This is because Siak is a Malaysian region that is rich in Islamic culture. But the reality shows that the saving and lending activities of BUMdes-BUMdes were not carried out according to the sharia concepts. The expected progress of BUMdes is certainly progress that is following Islamic values. Islamic values ​​always encourage the achievement of progress in a healthy, Islamic, honest, and blessing. Blessing is impossible to achieve if the companies carried out are still in conflict with the Sharia principles. It is hoped that the advanced BUMdes will be BUMdes whose presence is felt by the community and does not suffocate the community.